Efectos De Un Programa De Juegos De Velocidad, Coordinación Y Precisión, Para La Agilidad En Niños De Quinto De Primaria (2015)
This research deals with effects of game programs for agility fifth-grade children, whose objective was to determine the effect of a game show speed, coordination and precision on developing agility in fifth grade children. The methodology used was based on the application of the test of Illinois, which is a test that measures the speed and agility capacity resulting from the physical and coordinative abilities in subjects. The research process was developed with 14 boys and 9 girls with a mean age 0.59 ± 9.9 years. To whom was applied a game show based on speed, coordination and precision for 12 weeks. The results obtained in the pretest were 20.39 seconds and 20.16 in the post, without reaching significant (p = 0.312). The findings indicate that the implementation of a program for change in agility, should take into account the principles of sports training to develop explosive speed and strength; as well as specific exercises with changes in direction, speed of reaction to be performed continuously for all sessions.